Perception of The Stakeholders of The Romanian Banking System on The Adequacy of Current Accounting Regulation - Denis Adrian Levanti; Aurelia Stefanescu; Ileana Cosmina Pitulice (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What is the perception of the stakeholders of the Romanian banking system on the adequacy of current accounting regulations? Motivation- The motivation of this research is supported by the existence of a gap in the specialised literature: the perception of the interested parties of the banking sector regarding the degree to which the new financial reporting standards, IFRS 9, IFRS 15 and IFRS 16 have achieved their main objectives, that is if the information presented in the financial statements is sufficient in forming decisions by users. Research also aims to determine the suitability of accounting regulations in the context of the emergence of new risks affecting the banking sector, for instance COVID-19 pandemic and the risk of global climate change. Idea- The basic research idea is the analysis of the Romanian banks' stakeholders' perception regarding the degree of adequacy of the accounting regulatory framework in the current economic context and emerging risks. Data- The data was collected from 104 stakeholders, distributed into four groups. Tools- The online questionnaire survey strategy was used to collect the data. Analyses were conducted using the R programming language. To identify the factors that influenced the perceptions of the stakeholders and the differences in the respondent groups, Kruskal-Wallis and Mann-Whitney tests were applied. Findings- Stakeholders expressed a high level of agreement on the extent to which IFRS 9 has achieved its main objectives, that is to simplify the way financial instruments are accounted for and the early recognition of impairment adjustments. Also, stakeholders consider that national regulations and EBA's instructions and guidelines should be amended to provide clarifications regarding the application of IFRS principles in estimating the effects of emerging risks affecting the banking sector. Contribution- Addresses a gap in the specialized literature by investigating the perception of stakeholders regarding the implementation of the IFRS reform in recent years in the Romanian banking sector. Provides the local regulator with evidence regarding the accounting rules that, from the perspective of the interested parties, require changes to facilitate the process of estimating the effects of emerging risks on the financial performance of credit institutions.
Keywords: M41; M42; 650; banking sector; stakeholders; IFRS; accounting professionals; internal auditors; external auditors